Desarrollo de un Prototipo de Software en Python con Técnicas de Machine Learning para el Análisis de Datos Astronómicos de Exoplanetas Recopilados por la NASA - Rincón Valencia, Kimberly Johana (Universidad Antonio Nariño, 2021)
ML techniques and algorithms have become very important in the field of astronomy and in many other fields, due to the enormous volume of images or data collected using different means, derived from the study carried out in each area of knowledge and that generates the need from working with large and complex data groups (Big Data) to process, analyze and later make observations that allow extracting new knowledge to predict future behavior of said information.